CLARENCE WALTON LILLEHEI (1918–1999): WORK TO EXHAUSTION, PLAY UP TO THE END! - K. V. Litovka; A. M. Namitokov; S. T. Enginoev (Инновационная медицина Кубани)
The history of cardiovascular surgery development strikes with courage of the ideas. Takeoff and falling, success and defeats — all these were on the way of formation of cardiac surgery, but without mistakes and failures dynamic development of medicine is generally impossible.One of the outstanding cardiac surgeons, whose name will remain in the history forever is Walton Lillehei, the person whose keynote was «work to exhaustion, and play up to the end». Despite vicissitudes of life, he was not afraid to take the risk, understanding that in case of success, hundreds of lives would be saved. But at the same time his activity was not thoughtless passion, and on the contrary, each step of his, attempt of improvement or development of something new, whether it was surgical technique or introduction of a new device, had the soil of long researches and clinical observations.